Assessment of heavy metals and human health risk in shrimps collected from different farms at City of Mati, Davao Oriental - Roselyn V. Regino; Janeth C. Tayone; Geralph Sam P. Villarubia; Carmela May Albios; Rogie Mart B. Ambasan; Lorjie B. Bation; Joselle Marie P. Deaño; Wilanfranco C. Tayone (The Palawan Scientist, 2026)
Heavy metals are naturally occurring elements whose concentrations may increase due to anthropogenic activities, posing risks to ecosystems and human health. This study investigated the concentrations of cadmium, chromium, iron, lead, manganese, and nickel in water, sediment, and shrimp (tissue and shell) samples from selected farms in Barangays Dahican and Dawan, City of Mati, Davao Oriental, Philippines. Atomic Absorption Spectrometry was used for heavy metal study, and potential non-carcinogenic health risks were assessed using the target hazard quotient (THQ) and hazard index (HI), following the US Environmental Protection Agency guidelines. Results showed that chromium and nickel levels in water from both farms exceeded the allowable thresholds set by the Department of Environment and Natural Resources. In sediments, chromium, iron, lead, and manganese levels in Dahican exceeded World Health Organization (WHO) limits, whereas Dawan showed elevated levels of chromium, iron, and manganese, with nickel surpassing National Oceanic and Atmospheric Administration standards. In shrimp tissue, chromium in Dahican and manganese in Dawan exceeded WHO limits, while iron remained within safe limits. Cadmium, lead, and nickel were either undetected or below detection limits in shrimp tissue and shell samples from both farms. Despite the elevated concentrations of some metals in the samples, the THQ and HI were below one, indicating that long-term, continuous intake of shrimp from the two farms is unlikely to pose any significant health hazards. Nonetheless, continuous monitoring and management of heavy metals in shrimp farming remain essential to prevent future contamination risks and safeguard environmental and public health.